STRATEGI PENINGKATAN KUALITAS BATIK MELALUI PELATIHAN DI DESA MACAJAH KECAMATAN TANJUNG BUMI - MADURA - Nanik Farida; Mei Indrawati (Prodi Magister Manajemen Universitas Wijaya Putra, 2023)
Batik is a cultural heritage from our ancestors which is still developing in various regions in Indonesia. Batik cloth is worn as a characteristic of clothing in Indonesia which is used by all groups. Tanjung Bumi sub-district is known for the quality of hand-made batik which has different motifs and variations from other batik. Batik, which is also one of the world's cultural heritages, is a superior product and the pride of Tanjung Bumi sub-district. In the past, batik Tanjung Bumi was a job for women in the area to fill their spare time waiting for their husbands who worked as sailors to go to distant areas, such as to the islands of Kalimantan and Sulawesi. The results obtained are that Tanjung Bumi written batik can increase the income of Macajah Village. In the process of making written batik, the initial cultivation of batik focused on the motifs and colors on the batik cloth and made the villagers as workers thus helping the welfare of the people of Macajah Village.